PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI E-BUSINESS PADA CV DCP - Etin Puspita Sari; Mochamad Fatchurrohman; Fajar Tenovita Sari (Bajang Institute, 2024)
Data innovation can drive industries and change the way businesses are run. It is not appropriate for the role of e-business information and communication technology to be the main choice in the digital 4.0 era. Due to the growing development of technology in the digital era. Many large companies have used e-commerce information and communication technology to rethink their business strategy. Information and communication technology is a support in the success of a company's product marketing strategy. Technology is a major asset where it is easier for companies to reach customers in global market competition. Information and communication technology or abbreviated as ICT are all technologies related to information handling. Meanwhile, e-business is a business activity involving information systems that are connected to one another and computerized. In this study using a qualitative descriptive analysis research method with the assignment method of interviews. The purpose of this study is to provide an overview of how beneficial the use of e-business information and communication technology is in the hope that all employees can take advantage of e-business information and communication technology systems. Because the large number of respondents chose the strategy of utilizing e-business technology and information, it is appropriate for the government to provide support and monitoring in the form of training and technical guidance within a company for the sake of progress and trade competition in the digital era. Where a company must necessarily follow the development of the era which is increasing in terms of information technology and e-business communication.